Pelatihan Dokter Kecil Sebagai Upaya Mengembangkan Usaha Kesehatan Sekolah di Sekolah Dasar Kabupaten Sidoarjo - Andika Aliviameita; Yanik Purwanti; Arief Wisaksono (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2019)
The introduction of a healthy way of life must be done early, and can be started from family and school life. Health care for school-age children can be done through Usaha Kesehatan Sekolah (UKS). The UKS program can be used for coaching in the health sector that requires training of little doctors. The purpose of this activity is to provide training on basic medical materials to improve healthy and healthy living skills, the health status of students, and create a healthy environment so as to increase optimal growth and development. Obtained from the results of this training a positive influence on improving the ability of little doctors. Providing little doctor training provides learning that results in changes from the beginning. This activity involved 42 little doctors from two elementary schools in Sidoarjo. The level of understanding was good, the little doctors rose from (10 students) 23,8% to 69,1% (29 students), quite good understanding from 47,6% (20 students) to 21,4% (9 students), and of the 28,6% (12 students) it dropped to 9,5% (4 students) after receiving a small doctor training.